Review of Insulin Resistance in Dilated Cardiomyopathy and Implications for the Pediatric Patient Short Title: Insulin Resistance DCM and Pediatrics - Mak, Daniel; Ryan, Kaitlin A.; Han, Joan C. (Frontiers in Pediatrics, 2021)
Energy metabolism in the heart is affected during states of dysfunction. Understanding how the heart utilizes substrates in cardiomyopathy may be key to the development of alternative treatment modalities. Myocardial insulin resistance has been proposed as a possible barrier to effective glucose metabolism in the heart. Extensive literature on the topic in adult individuals exists; however, review in the pediatric population is sparse. The pathophysiology of disease in children and adolescents is unique. The aim of this paper is to review the current knowledge on insulin resistance in dilated cardiomyopathy while also filling the gap when considering care in the pediatric population.